Analisa Indeks Kinerja Sistem Irigasi Pada Daerah Irigasi Batang Sangkir Kab. Kerinci - Dimas Adi Prasetio; Azwarman Azwarman; Susiana Susiana (Universitas Batanghari Jambi, 2022)
Batang Sangkir Irrigation Area in Kerinci district was built in 1984. Over time, the function of irrigation network services has decreased, so the operation and maintenance of irrigation networks is an activity that is very much needed to keep irrigation network performance maintained. In this regard, an assessment of the Irrigation System Performance Index in the Batang Sangkir Irrigation Area needs to be carried out to assess aspects or components that are not yet optimal in this irrigation area for immediate special handling or improvement. The assessment begins with an inventory of the condition and function of physical infrastructure, crop productivity results, supporting facilities, organization, documentation and P3A institutions to determine the performance value and recommendations for handling it. The results of the irrigation system performance index in the Batang Sangkir irrigation area are 63.47% which is included in the performance category is not good and needs attention. With the value of physical infrastructure 30.40%, crop productivity 13.80%, supporting facilities 3.43%, documentation 3.50% and P3A institutional 1.65%. Based on the value of this performance index, special maintenance and repair of physical facilities is required. at several points that were damaged, facilitated supporting facilities for OP officers so that officers were more agile in their activities, and gave P3A more attention so that they could contribute to maintaining and making good use of Batang Sangkir irrigation in the future.